Consumer Protection Against Unauthorized Charges in Subscription-Based Parking System in Medan: A Legal Analysis from the Perspective of Istishab - Annisa Filjannah; Rahmat Hidayat (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2025)
The imposition of unauthorized charges on subscription-based parking consumers in Medan City undermines legal certainty and causes significant economic and psychological harm. Although designed to ensure convenience and protection, the subscription parking system has failed to prevent double charging, exposing the weakness of current consumer protection mechanisms. This study analyzes legal protection for subscription parking consumers by integrating positive law and the Islamic legal principle of istishab. Using empirical legal research with a qualitative approach, data were collected through literature review, in-depth interviews with consumers and parking attendants, and analysis of regulatory documents. Findings reveal that consumers suffer ongoing financial losses and distress despite fulfilling their legal obligations, while weak supervision and misaligned revenue-sharing mechanisms perpetuate unauthorized levies. From an istishab perspective, consumers’ rights remain valid unless lawfully nullified, rendering such charges a violation of both positive and Islamic law. The study proposes an integrative framework for consumer protection, recommending stricter enforcement, restructuring revenue-sharing schemes, and improving attendant education to restore public trust.